2019
DOI: 10.3171/2019.1.focus18572
|View full text |Cite
|
Sign up to set email alerts
|

Rotational thromboelastometry–guided transfusion during lumbar pedicle subtraction osteotomy for adult spinal deformity: preliminary findings from a matched cohort study

Abstract: OBJECTIVESignificant blood loss and coagulopathy are often encountered during adult spinal deformity (ASD) surgery, and the optimal intraoperative transfusion algorithm is debatable. Rotational thromboelastometry (ROTEM), a functional viscoelastometric method for real-time hemostasis testing, may allow early identification of coagulopathy and improve transfusion practices. The objective of this study was to investigate the effect of ROTEM-guided blood product manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…FIBTEM MCF has been also used in several ROTEM-based algorithms for individualized hemostatic therapy to decrease transfusion requirements. [28][29][30][31][32][33][34][35][36][37] However, since studies aiming to identify the FIBTEM MCF value that predicts better and increased probability for transfusion are lacking, the cut-off value that has been used in those algorithms is not consistent. In some algorithms the cut-off value was selected based on author's preference, whereas in many others a value close to the reported lower reference range was chosen (►Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…FIBTEM MCF has been also used in several ROTEM-based algorithms for individualized hemostatic therapy to decrease transfusion requirements. [28][29][30][31][32][33][34][35][36][37] However, since studies aiming to identify the FIBTEM MCF value that predicts better and increased probability for transfusion are lacking, the cut-off value that has been used in those algorithms is not consistent. In some algorithms the cut-off value was selected based on author's preference, whereas in many others a value close to the reported lower reference range was chosen (►Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of patients undergoing major spinal surgery ROTEM (ROtational ThromboElastoMetry) device used with TXA was found to lead to a significantly lower blood loss and lower transfusion of packed red blood cells as compared to the TXA alone (123). Other studies have demonstrated the utility of ROTEM in decreasing the rate of blood product transfusion (124, 125).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of patients undergoing major spinal surgery ROTEM (ROtational ThromboElastoMetry) device used with TXA was found to lead to a significantly lower blood loss and lower transfusion of packed red blood cells as compared to the TXA alone [126]. Studies have demonstrated the utility of ROTEM in decreasing the rate of blood product transfusion [127,128].…”
Section: Perioperative Blood Conservation Strategiesmentioning
confidence: 99%